The UNESCO concept of biosphere reserves - Jeżyńska, Beata; Pastuszko, Radosław (Przegląd Prawa Rolnego, 2021)
Sustainable development and problems related to it are currently the subject of interest of numerous scientific, governmental and social bodies, and the discussion that is going on concerns all levels and types of environmental pressures. Therefore, the activities undertaken by UNESCO that aim at creating a platform for sustainable interaction in the form of biosphere reserves should be considered as worthy of presentation here. They constitute an exceptional manifestation of the implementation of the sustainable development principle in practice.